HARMONIZATION OF KNOWLEDGE AND QUALITIES OF PERSONALITY DURING STUDENTS' DISCIPLINES HISTORICAL AND PEDAGOGICAL CYCLE - V.V. Sadova (Academy of Cognitive and Natural Sciences, 2010)
The article highlights some possible ways for harmonization of knowledge and personality's features of students in the process of educational course History of Pedagogy studies. Emphasized the concept of comparativistics activating improves gaining program knowledge and forms necessary personality's features of a pedagogue-to-be.